SISTEM PAKAR IDENTIFIKASI FAKTOR-FAKTORYANG MEMPENGARUHI PSIKOLOGIS TERHADAP ANAKMENGGUNAKAN METODE FORWARD CHAINING. - Hamdhany Abdhi Kurnia, (2020)
This psychological expert system is designed to make parents realize that psychological health is very disruptive to children's development if left unchecked. This expert system helps parents to find out what diseases their children have and also provides the right solutions to deal with them. The method used in this expert system is forward chaining, this method will later process any symptoms that are felt and the results will show a solution according to the symptoms of the disease that has been selected. This system is expected to be able to open up parents' views of how important it is to maintain health, not only visible physical health. With the right solution provided by the system, it is also hoped that it will be able to help early detection or relieve the psychological illness suffered by the child before the disease is very attached to it.